2022
DOI: 10.1007/s10067-022-06067-5
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic SARS-CoV-2 seropositivity: patients with childhood-onset rheumatic diseases versus healthy children

Abstract: Objective We aimed to find out the asymptomatic severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) seroprevalence among pediatric patients with rheumatic diseases and healthy children and to compare them with each other. Methods Patients with familial Mediterranean fever (FMF), juvenile idiopathic arthritis (JIA), and juvenile systemic lupus erythematosus (jSLE) and healthy children as healthy control (HC) group who remained asymptomatic during the pandemic ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Patients with SARS-CoV-2 infection who are known to have a history of autoimmune rheumatic disease and undergoing immunomodulatory treatment are not at high risk of developing severe forms of COVID-19 or complications [ 19 ]. The results of Haslak et al suggested that patients with childhood onset rheumatic diseases, even if treated with immunosuppressive medication might have an asymptomatic SARS-CoV-2 infection, presenting similarly to healthy individuals [ 20 ]. According to current studies, some of disease modifying antirheumatic drugs (DMARDs) used by SLE patients have certain effects on COVID-19, influencing the risk of acquiring the infection, disease progression and the immunogenicity of vaccines.…”
Section: Epidemiology and Risk Factors For Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with SARS-CoV-2 infection who are known to have a history of autoimmune rheumatic disease and undergoing immunomodulatory treatment are not at high risk of developing severe forms of COVID-19 or complications [ 19 ]. The results of Haslak et al suggested that patients with childhood onset rheumatic diseases, even if treated with immunosuppressive medication might have an asymptomatic SARS-CoV-2 infection, presenting similarly to healthy individuals [ 20 ]. According to current studies, some of disease modifying antirheumatic drugs (DMARDs) used by SLE patients have certain effects on COVID-19, influencing the risk of acquiring the infection, disease progression and the immunogenicity of vaccines.…”
Section: Epidemiology and Risk Factors For Covid-19mentioning
confidence: 99%
“…Type I interferon responses seem to be strong in relation to COVID-19 infections [ 38 ]. An increased expression of IFN-α has been observed in many patients with autoimmune pathology, especially in SLE patients [ 20 ]. Over time, SLE onset has been associated to previous viral exposure such Epstein–Barr virus (EBV), parvovirus, cytomegalovirus (CMV), hepatitis C virus and, more recently, SARS-CoV-2 [ 39 , 40 , 41 ].…”
Section: Pediatric Sle Onset Following Covid-19mentioning
confidence: 99%
“…Similar studies in children with rheumatic diseases have been conducted in other countries [8][9][10]. In a study conducted in Turkey from March 2020 to August 2020 [8], exactly in the period of our first study [4], 149 children asymptomatic for COVID-19 (43 healthy children, 42 with JIA, and 64 with other rheumatic diseases) were included.…”
Section: Discussionmentioning
confidence: 91%
“…Similar studies in children with rheumatic diseases have been conducted in other countries [8][9][10]. In a study conducted in Turkey from March 2020 to August 2020 [8], exactly in the period of our first study [4], 149 children asymptomatic for COVID-19 (43 healthy children, 42 with JIA, and 64 with other rheumatic diseases) were included. The proportion positive for anti-SARS-CoV-2 IgA or IgG was 12.75% children, including 18.6% healthy children and 11.9% diagnosed with JIA, but those differences were not statistically significant.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation